Myeloid sarcoma in children – diagnostic and therapeutic difficulties - Samborska, Magdalena; Derwich, Katarzyna; Skalska-Sadowska, Jolanta; Kurzawa, Paweł; Wachowiak, Jacek (Contemporary Oncology/Współczesna Onkologia, 2016)
Myeloid sarcoma (MS) is a malignant extramedullary tumour, which consists of immature cells of myeloid origin. It may occur de novo , concurrently or precede the diagnosis of acute myeloid leukemia (AML), myelodysplastic syndrome (MDS) or chronic myeloid leukemia (CML). MS can also be a manifestation of the relapse of the disease. The more frequent sites of involvement are the skin, orbit, bone, periosteum, lymph nodes, gastrointestinal tract, soft tissue, central nervous system and testis. Because of its different localization and symptoms, and the lack of diagnostics algorithm, myeloid sarcoma is a real diagnostic challenge, in particular in patients without initial bone marrow involvement. The correct diagnosis of MS is important for adequate therapy, which is often delayed because of a high misdiagnosis rate. In the paper, the role of immunohistochemistry, cytogenetic and molecular genetic analyses is emphasized as well as the breadth of unclear aspects of this disorder in children.